2021
DOI: 10.5039/agraria.v16i3a132
|View full text |Cite
|
Sign up to set email alerts
|

Morphophysiology and nutrition of yellow passion fruit seedlings grown in substrates based on carnaúba palm bagana

Abstract: The use of agro-industrial waste may represent an alternative to reduce the costs of purchasing commercial substrates by producers of passion fruit seedlings, and carnaúba palm bagana is an alternative for the Northeastern Brazilian region. In this context, the objective was to evaluate the production of yellow passion fruit seedlings in substrates based on carnaúba bagana in different proportions with soil. The experiment was conducted in the experimental area of the Agrometeorological Station of Fortaleza, P… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
1
0
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 7 publications
2
1
0
1
Order By: Relevance
“…The carnauba bagana increments in the substrates also increased the levels of organic matter and macronutrients (N, P, K, Ca, Mg and S) (Table 2). This result is consistent with those of previous studies (Costa et al 2021, Mendonça et al 2021, which found that an increase in the proportion of organic residues in the substrate increases the levels of macronutrients. For cultivation in containers, a high organic matter content is desirable, considering the sporadic supply of water and nutrients (Schmitz et al pH: hydrogen potential; OM: organic matter; N: nitrogen; P: phosphorus; K: potassium; Ca: calcium; Mg: magnesium; S: sulfur.…”
Section: Resultssupporting
confidence: 94%
See 1 more Smart Citation
“…The carnauba bagana increments in the substrates also increased the levels of organic matter and macronutrients (N, P, K, Ca, Mg and S) (Table 2). This result is consistent with those of previous studies (Costa et al 2021, Mendonça et al 2021, which found that an increase in the proportion of organic residues in the substrate increases the levels of macronutrients. For cultivation in containers, a high organic matter content is desirable, considering the sporadic supply of water and nutrients (Schmitz et al pH: hydrogen potential; OM: organic matter; N: nitrogen; P: phosphorus; K: potassium; Ca: calcium; Mg: magnesium; S: sulfur.…”
Section: Resultssupporting
confidence: 94%
“…The use of carnauba bagana has been reported in the literature as an alternative substrate source and has shown satisfactory results in the production of seedlings of various species (Lustosa Filho et al 2015, Sousa et al 2020, Mendonça et al 2021). However, no study has evaluated the potential of carnauba bagana as a substrate for producing presprouted sugarcane seedlings.…”
Section: Abstract Resumomentioning
confidence: 99%
“…The values of dry biomass of the seedlings produced on the growing medias that stood out in this study were comparable to or exceeded those described in the literature (Muniz et al, 2020;Cordeiro et al, 2019). However, in certain cases, they were lower which could be attributed to the differences in the cultivars and management practices adopted during seedling production (Mendonça et al, 2021).…”
Section: Resultssupporting
confidence: 81%
“…O uso de substratos alternativos formulados a base de bagana de carnaúba [12][13][14] e casca de arroz carbonizada [15] são consideradas alternativas ambiental e economicamente sustentáveis, podendo ser empregado na produção de mudas de diferentes culturas. Adicionalmente, o uso de chorume também já foi relatado para a nutrição de plantas [16][17][18]11] e na indução a resistência ao estresse [19].…”
Section: Introductionunclassified